Reflexões sobre morte e legado na educação : ressignificação da vida expressa por jovens do ensino médio - Trevisan, Daniele (2023)
Since modernity, a relationship of distance, fear and denial regarding death has been established. However, it brings with it potential that allows us to learn to live better. When we reflect on life from the perspective of finitude, we reevaluate the varied themes and values that permeate our existence. In this way, we believe that reflection on the finiteness of life provides us with the construction of existence based on more reflective and critical attitudes that result in concern with an ethical stance in the construction of existence. The school, as a space for human formation, can contribute to this process, however, death continues to be veiled in educational environments, thus persisting a gap in the treatment of this topic. Faced with these questions, we ask ourselves: How can we approach the issue of death with young people in high school in a way that contributes to reflections that enable the reframing of life? In this sense, the general objective of the research was to understand how young people perceive, reflect and relate to human finitude and how the discussion of this topic can contribute to existential reflections and the new meaning of life by high school students in a public school in the state of Mato Grosso. From a methodological point of view, the research was developed based on a qualitative approach through participatory research methodology. Data collection comprised three phases: i) theoretical, institutional and methodological planning, at which time we carried out a theoretical study of authors who discuss the educational aspects of death and a Systematic Literature Review, we defined the locus of research and carried out the regulations to comply with the necessary ethical precepts; ii) the definition of the research group and diagnosis of reality, a presentation and invitation to young people to participate was carried out, we carried out individual interviews for an initial diagnosis with the participating students and the analysis of data from these interviews that allowed us to identify the themes that would be addressed in the research process; iii) planning and carrying out educational strategies, we built a pedagogical program that conducted training meetings with students participating in the research, twenty-three meetings were held in the months of October and November of 2021. All actions were carried out at the State School José Alves Bezerra, a public school in the state education network in the state of Mato Grosso, located in the municipality of Porto dos Gaúchos/MT and had the participation of 31 students enrolled in high school at this institution. The analysis of the collected data was carried out using categorical content analysis (Bardin, 2016). The categorization referring to the initial interview that consisted of diagnosing reality resulted in categories that later, in relation to the theoretical framework, themes emerged that would be addressed in the training meetings. From the analysis of the results, we realized that for the discussion about death, the need for discussions that contributed to understanding the taboo and prohibition on death emerged from the students, given the lack of spaces for clarification of doubts. We hold discussions about immortality and different views on death from a historical and cultural perspective. The theme of human finitude also emerged several reflections on existence, in this age group, we highlight the challenges of adolescence, relationships and self-destructive behaviors. We also highlighted the need for an approach to grief, given the difficulty they presented in understanding the meanings of rituals and dealing with situations of loss, both in overcoming and in supporting family and friends. From the discussions held, we realized that it is possible to build social practices based on a conscious relationship with finitude and reflections on human existence that lead to the creation of different ways of dealing with death and mourning.